Mavie: Natural Antiseptic Spray with Rose and Vetiver Extracts - Ghaitsa Nurnazma; Zaira Janeeta Akmalul Iman; Amiratus Saidah; Ariani Pratiwi; Nadiva Firya Khamdani; Syifa Aryanti; Agung Taufik (GLOBAL SCIENTS PUBLISHER, 2026)
This study aimed to formulate and evaluate a natural antiseptic spray using plant-based ingredients derived from vetiver (Vetiveria zizanoides) and rose (Rosa damascena). The research was conducted as a school-based project focusing on simple formulation and descriptive observation rather than advanced laboratory analysis. Vetiver extract was obtained through a basic steam distillation process, while rose extract was prepared using water-based maceration. Both extracts were combined with a bioethanol-based solvent to produce a natural antiseptic spray formulation. The evaluation of the product focused on observable characteristics, including aroma, appearance, ease of use, and user response. Limited testing was carried out through non-clinical observation to assess user acceptance and potential irritation after short-term use. The results showed that the antiseptic spray had a pleasant natural aroma and was well accepted by users. No visible adverse reactions such as redness, itching, or discomfort were reported during limited observation. Based on these findings, the formulated antiseptic spray demonstrates potential as a natural and environmentally friendly product for external use. However, this study did not include chemical composition analysis, antioxidant testing, or microbiological assays. Therefore, the results are limited to formulation outcomes and user acceptance. Further research involving controlled laboratory testing is recommended to evaluate the chemical properties and antimicrobial effectiveness of the product.